2019
DOI: 10.1073/pnas.1906036116
|View full text |Cite
|
Sign up to set email alerts
|

Two PKA RIα holoenzyme states define ATP as an isoform-specific orthosteric inhibitor that competes with the allosteric activator, cAMP

Abstract: Protein kinase A (PKA) holoenzyme, comprised of a cAMP-binding regulatory (R)-subunit dimer and 2 catalytic (C)-subunits, is the master switch for cAMP-mediated signaling. Of the 4 R-subunits (RIα, RIβ, RIIα, RIIβ), RIα is most essential for regulating PKA activity in cells. Our 2 RIα2C2 holoenzyme states, which show different conformations with and without ATP, reveal how ATP/Mg2+ functions as a negative orthosteric modulator. Biochemical studies demonstrate how the removal of ATP primes the holoenzyme for cA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 55 publications
(75 reference statements)
4
37
0
Order By: Relevance
“…Once activated by cAMP, the B/C/N-helix divides into 3 segments (B-helix, C-helix, and N-helix) ( Fig 2F and 2G). Several studies have already pointed out the importance of the flexibility of the B/C/N-helix in activation of the RIα holoenzyme [10,17,18]. Here, we show that the B/C/ N-helix is also very dynamic, but different, in the RIIβ holoenzyme.…”
Section: Riiβsupporting
confidence: 58%
See 1 more Smart Citation
“…Once activated by cAMP, the B/C/N-helix divides into 3 segments (B-helix, C-helix, and N-helix) ( Fig 2F and 2G). Several studies have already pointed out the importance of the flexibility of the B/C/N-helix in activation of the RIα holoenzyme [10,17,18]. Here, we show that the B/C/ N-helix is also very dynamic, but different, in the RIIβ holoenzyme.…”
Section: Riiβsupporting
confidence: 58%
“…The activity of PKA can be stimulated by the elevated concentration of cAMP, through binding of cAMP to R subunits which unleashes the activity. Each of 4 functionally nonredundant R subunit isoforms (RIα, RIβ, RIIα, and RIIβ) has distinct quaternary holoenzyme structures, cAMP sensitivity, and cellular localization [7][8][9][10][11]. All 4 R subunit isoforms share a similar domain organization which consists of an N-terminal Dimerization/Docking (D/D) domain followed by an intrinsically disordered linker that connects to 2 tandem cyclic nucleotide binding (CNB) domains.…”
Section: Introductionmentioning
confidence: 99%
“…The allosteric networks we describe here may be amplified in the PKA hetero-tetramer composed of two regulatory and two catalytic subunits, where the potential cross-talk between PKA subunits is expanded 12,34,40 . Structural studies of the PKA hetero-tetramer formed with RI isoforms showed the N3A motif of one regulatory subunit stacked against the N3A motif of the neighboring one, forming a helical bundle with several hydrophobic interactions 41,42 . Therefore, it is possible that the dynamic switching response of the N3A motif described here may play additional allosteric regulatory roles by communicating the two regulatory subunits in the PKA hetero-tetramer via quaternary interactions.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the mixed A off -B on excited state sampled by R AB :Rp 2 drives Rp to act as an antagonist when C binds R AB with sufficiently high affinity to selectively stabilize A off -B on relative to A on B on and A on -B on , resulting in a stable C:R AB :Rp 2 complex and PKA inhibition. However, if the affinity of C for R AB is reduced, for example, due to lower MgATP levels (28)(29)(30), the inhibitory A off -B on state remains excited in the presence of C, while the ground, most populated state is still A on B on , which, being inhibition incompetent, leads to PKA activation. Hence, the model of Fig.…”
Section: Wt R Ab :Rp 2 Samples a Conformational Ensemble With A Grounmentioning
confidence: 99%